Exhibition Reviews. (1st February 2016) - Weiner, Andrew Stefan; Mutlu, Rasit; Brown, Kathryn; MacInnis, Jordan; Bronstein, Noa; Mida, Ingrid
The Xerox Book Paula Cooper Gallery, New York, 12 September–24 October 2015Saltwater: A Theory of Thought Forms – 14th Istanbul Biennial Curated by Carolyn Christov-Bakargiev, various locations, Istanbul, 2 September–1 November 2015Ink Remix: Contemporary Art from Mainland China, Taiwan and Hong Kong Curated by Sophie McIntyre, exhibited at the Canberra Museum and Gallery, 3 July–18 October 2015; Bendigo Art Gallery, 31 October 2015–7 February 2016; University of New South Wales Galleries, 26 February–21 May 2016; Museum of Brisbane, 16 September 2016–19 February 2017Artist Textiles: Picasso to Warhol Curated by Dennis Nothdruft, Textile Museum of Canada, Toronto, 2 May–4 October 2015Mark Rothko's Harvard Murals Curated by Mary Schneider Enriquez, in collaboration with Narayan Khandekar, Carol Mancusi-Ungaro, Christina Rosenberger and Jens Stenger, Harvard Art Museums, Cambridge, 16 November 2014– 26 July 2015Dries Van Noten: Inspirations Curated by Pamela Golbin, with Karen Van Godtsenhoven, MoMu Fashion Museum, Antwerp, 13 February–19 July 2015, originally presented at Musée des Arts Décoratifs (curated by Pamela Golbin), Paris, 1 March–2 November 2014